Distribution of bacterial DNA repair proteins and their co-occurrence with immune systems - Sumanth K. Mutte; Patrick Barendse; Pilar Bobadilla Ugarte; Daan C. Swarts (Cell Reports)
Summary: Bacteria encode various DNA repair pathways to maintain genome integrity. However, the high degree of homology between DNA repair proteins or their domains hampers accurate identification. Here, we describe a stringent search strategy to identify DNA repair proteins and provide a systematic analysis of taxonomic distribution and co-occurrence of DNA repair proteins involved in RecA-dependent homologous recombination. Our results reveal the widespread presence of RecA, SSB, and RecOR proteins and phyla-specific distribution for the DNA repair complexes RecBCD, AddAB, and AdnAB. Furthermore, we report co-occurrences of DNA repair proteins with immune systems, including specific CRISPR-Cas subtypes, prokaryotic Argonautes (pAgos), dGTPases, GAPS2, and Wadjet. Our results imply that while certain DNA repair proteins and immune systems might function in conjunction, no immune system strictly relies on a specific DNA repair protein. As such, these findings offer an updated perspective on the distribution of DNA repair systems and their connection to immune systems in bacteria.